Conversations about Building Extension Capacity in Post-Conflict: A Review of Building Agricultural Extension Capacity in Post-Conflict Settings - Glen C. Shinn (Journal of International Agricultural and Extension Education, 2017)
McNamara and Moore (2017) have chosen to examine post-conflict environments—a significant and timely topic—and strategies for building extension capacity. As editors, McNamara and Moore provide an opportunity to engage in a roundtable with 20 authors. The composition deals with a dozen cases drawn from 11 countries on three continents—Africa, Asia, and North America. Based in North America, Europe, and Africa, the author team is well qualified. Christoplos closes with a Danish view of “what we know about the recovery process” and about “rebuilding extension from a political economy perspective” (p. 228). Christoplos’ call for ethics and evidence “… built on principles of participation, transparency, accountability and non-discrimination” (p. 241) position extension well in a turbulent world.
Keywords: Africa; Agriculture; Asia; Capacity-Building; Case Study; Extension; North America; Post-conflict; Poverty